Phosphodiesterase 10A Is a Mediator of Osteogenic Differentiation and Mechanotransduction in Bone Marrow-Derived Mesenchymal Stromal Cells. (6th June 2020) - Müller-Deubert, Sigrid; Ege, Carolin; Krug, Melanie; Meißner-Weigl, Jutta; Rudert, Maximilian; Bischof, Oliver; Jakob, Franz; Ebert, Regina
Abstract : Bone marrow-derived mesenchymal stromal cells (hMSCs) are capable of differentiating into the osteogenic lineage, and for osteogenic differentiation, mechanical loading is a relevant stimulus. Mechanotransduction leads to the formation of second messengers such as cAMP, cGMP, or Ca 2+ influx resulting in the activation of transcription factors mediating gene regulation. The second messengers cAMP and cGMP are degraded by phosphodiesterase isoenzymes (PDE), but the role of these enzymes during osteogenic differentiation or mechanotransduction remains unclear. Here, we focused on the isoenzyme phosphodiesterase 10A (PDE10A) and its role during osteogenic commitment and mechanotransduction. We observed a time-dependent decrease of PDE10A expression in hMSC undergoing differentiation towards the osteogenic lineage. PDE10A inhibition by papaverine diminished osteogenic differentiation. While applying mechanical strain via cyclic stretching of hMSCs led to an upregulation of PDE10A gene expression, inhibition of PDE10A using the drug papaverine repressed expression of mechanoresponsive genes. We conclude that PDE10A is a modulator of osteogenic differentiation as well as mechanotransduction in hMSCs. Our data further suggests that the relative increase of cAMP, rather than the absolute cAMP level, is a key driver of the observed effects.